(3Gdbje GdCNdGbjI hYdGbJgG HCSGdjH GdJfTFI GdhGdOjI dOi GdeQGgbGJ GdeMQheGJ CSQjG HeOjfI GdQjGV (B/s - (3RgQGf, fjajf eMeOs; (3GdeDef, ShSf HfJ YHO GdcQje Hf eMeOs; (3GdOhSQj, gjaGA HfJ THfGfs ((3GdeedcI GdYQHjI GdSYhOjI (B:s (3LGeYI Gdedc YHO GdYRjR, cQSj GdCejQ fGja Hf YHO GdYRjR ddbje GdCNdGbjI,s, 2017)
(3Je GdJWQb Edi OQGSI YOO ef Gdbje GdCNdGbjI hgj JMed GdeSDhdjI hGdGfJeGA hGdhdGA ddhWf hGdCeGfI ceG JgOa GdOQGSI CjVG Edi aMU fhY GdYdGbI GdGQJHGWjI Hjf Gdbje GdCNdGbjI hCSGdjH GdJfTFI GdhGdOjI ceG jOQcgG hjbQQgG GdCHfGA ef GdeQGgbGJ ef CSQ WHjYjI cPdc JSYi GdOQGSI Edi YbO ebGQfGJ Hjf CaQGO GdYjfI aj cd ef Gdbje GdCNdGbjI hCSGdjH GdJfTFI GdhGdOjI GdeOQcI hGdebQQI efgf hPdc aj VhA cd ef eJZjQj GdeQMdI GdOQGSjI (B((3GdeJhSWI(B-(3GdKGfhjI(B) (3hGdMGdI GdhGdOjI CLQjJ gPg GdOQGSI Ydi YjfI ef (B400 (3eQGgbI ef WGdHGJ GdeQMdJjf GdeJhSWI hGdKGfhjI HGdQjGV HGdeedcI GdYQHjI GdSYhOjI(B.s
(3JUeje GdZdGa (B: (3SGeM Nda(B.s
(3HHdjhLQGajI (B: (3UaMI (B88-101.s
Keywords: (3Gdbje GdGLJeGYjIs -- (3GdQjGVs -- (3HMhK hUajIs; (3GdBHGA hGdCHfGAs -- (3YdGbGJ CSQjIs -- (3LhGfH faSjIs -- (3GdSYhOjIs -- (3GdQjGVs